2015
DOI: 10.1016/j.jaci.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 inhibits peanut-induced basophil and mast cell activation in peanut-tolerant children sensitized to peanut major allergens

Abstract: BackgroundMost children with detectable peanut-specific IgE (P-sIgE) are not allergic to peanut. We addressed 2 non–mutually exclusive hypotheses for the discrepancy between allergy and sensitization: (1) differences in P-sIgE levels between children with peanut allergy (PA) and peanut-sensitized but tolerant (PS) children and (2) the presence of an IgE inhibitor, such as peanut-specific IgG4 (P-sIgG4), in PS patients.MethodsTwo hundred twenty-eight children (108 patients with PA, 77 PS patients, and 43 nonsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(257 citation statements)
references
References 36 publications
14
229
4
3
Order By: Relevance
“…Recent data support a relevant suppressive effect of IgG4 in patients that acquired tolerance to peanut or keep a status of tolerance despite sensitization. IgG4 from peanut-sensitized nonallergic individuals suppressed allergen-specific activation of mast cells and basophils loaded with IgE from allergic individuals (121), although other studies showed that allergen-specific IgG seems not to be involved in peanut natural clinical tolerance (111).…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 95%
“…Recent data support a relevant suppressive effect of IgG4 in patients that acquired tolerance to peanut or keep a status of tolerance despite sensitization. IgG4 from peanut-sensitized nonallergic individuals suppressed allergen-specific activation of mast cells and basophils loaded with IgE from allergic individuals (121), although other studies showed that allergen-specific IgG seems not to be involved in peanut natural clinical tolerance (111).…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 95%
“…This absence of any IgE dose-response is also observed during omalizumab treatment of chronic urticaria [144]. This discrepancy could relate to the existence of neutralising antibodies towards IgE, which was recently established ex vivo [145,146], providing new evidence that the IgE level alone might not be sufficient to predict clinical outcome. It is also possible that IgE may act on mast cells independently of allergen-induced IgE/receptor cross-linking, to promote their survival and decrease their activation threshold by other stimuli, as suggested in the skin [147].…”
Section: Ige As a Therapeutic Target And A Biomarker In Asthmamentioning
confidence: 99%
“…Supporting this, symptom severity during failed oral food challenges correlated with basophil reactivity [65]. Basophil and mast cell activity in vivo depends on both the IgE affinity and concentration, and also on competing IgG4 to the same allergen [66]. Although hydrolysates of peanut flower appeared to reduce the molecular weight of allergens, the basophil reactivity of peanut-allergic patients was not reduced by this treatment, suggesting that IgE epitopes were predominantly linear, and peptides containing IgE epitopes were resistant to degradation [67].…”
Section: Progress In the Diagnosis And Monitoring Of Allergy By Basopmentioning
confidence: 99%